Qualche ‘aggiustamento’ alla disciplina dei magistrati vaticani. : Criticità della Lettera Apostolica in forma di «Motu Proprio» del Sommo Pontefice Francesco recante modifiche alla Legge sull’ordinamento giudiziario, alla Legge recante disposizioni per la dignità professionale e il trattamento economico dei magistrati ordinari del Tribunale e dell’Ufficio del Promotore di giustizia e al Regolamento Generale del Fondo Pensioni del 27 marzo 2024 (Stato, Chiese e pluralismo confessionale, 2024)
Some ‘adjustments’ to the regulations on Vatican magistrates. Criticalities of the Apostolic Letter in the form of a «Motu Proprio» by the Supreme Pontiff Francis amending the Law on the Judicial Order, the Law on Provisions for the Professional Dignity and Economic Treatment of Ordinary Magistrates of the Court and the Office of the Promoter of Justice and the General Regulations of the Pension Fund dated March 27, 2024ABSTRACT: The essay examines the content of the recent Apostolic Letter in the form of a “Motu Proprio” through which significant changes were introduced in relation to the office and status of Vatican magistrates, about multiple profiles (from those concerning the discipline of civil liability to those in economic and social security matters) from which a general trend in their favor emerges. They appear all the more noteworthy in consideration of the peculiar moment in which they were adopted, placing themselves on the sidelines of a court case which, in its own way, can offer at least some suggestions in their regard. In particular, however, the changes that were made find a considerably useful term of comparison not only in the situation prior to the reform, but above all in the innovations that have affected canon law in recent years (from which one can notice the recurrence of errors of legislative drafting of a similar nature) and in the Italian discipline regulating the same matter (from the observation of which potentially revealing analogies and divergences become evident).SOMMARIO: 1. Un’analisi su più fronti - 2. Tre nuclei tematici differenti ma correlati. La cessazione dell’ufficio di magistrato - 3. La responsabilità civile dei magistrati: una comparazione tra normativa vaticana e normativa italiana - 4. Segue: divergenze significative e lacune problematiche - 5. Il trattamento economico dei magistrati.